Pembuatan Website, Instagram Dan Akun Shopee Sebagai Media Marketing Produk Anyaman Bambu Di Desa Duwet - Putri Elfa Mas`udia; Rieke Adriati Wijayanti; Moh. Abdullah Anshori; Lis Diana Mustafa; Mochammad Sarosa; Yani Ratnawati (Universitas 45 Surabaya, 2023)
Desa Duwet is a village located in the Tumpang sub-district of Malang Regency. The majority of the residents work as farmers and engage in Micro, Small, and Medium Enterprises (MSMEs). There are several creative industries, such as crafts made from various bamboo products (besek), satay skewers, various banana-based pastries, and the production of cookies. The besek bamboo crafts are of good quality and should be sold at competitive prices.. The main challenges faced are the lack of promotional techniques and marketing supported by digital information technology through offline and online marketing platforms. A team from the State Polytechnic of Malang helps the village of Duwet with marketing through digital media by creating a website, Shopee account, and Instagram account so that the sales of besek bamboo crafts can be directly from end to end to the customers.